Influence of exogenous ascorbic acid on vase life and biochemical constituents of chrysanthemum (Chrysanthemum × morifolium.) - HIREMATH, VARUN M; JAIN, RITU; SINHA, NIVEDITA (The Indian Journal of Agricultural Sciences, 2019)
The present investigation was conducted at IARI, New Delhi in the year 2015-16 to examine the effect of ascorbic acid on changes in level of physiological and biochemical constituents during the postharvest life of chrysanthemum cv. Pusa centenary. The study revealed that spraying of ascorbic acid on the surface of cut flowers enhanced the vase life of cut flowers compared to control. Ascorbic acid sprays conserved the chlorophyll a, b and total chlorophyll content in leaves up to 14 days after harvest (S3). Total carotenoid content in leaves was found highest just after harvest (S1) and gradually declined as the senescence progressed from S1 to S2. Spraying 100 ppm ascorbic acid (T3) to cut flowers showed higher membrane stability compared to control in S3. Higher amount of H2O2 in control was due to enhanced activity of SOD enzyme as it dismutates superoxide radicals produced over senescence period. Decreased activity of ascorbate peroxidase in control during S2 and S3 might have led to excess accumulation of H2O2.Significantly higher CAT activity was found after spraying with 100 ppm ascorbic acid at 7 days after harvest (S2) compared to control. Progress of flower senescence was delayed by the coordinated antioxidant action of SOD, POX and CAT enzymes by maintaining their constant level at S2 and S3. This study concludes that spraying ascorbic acid to harvested cut flowers delayed early leaf yellowing and petal senescence in chrysanthemum.